Hematology and Biochemistry Panel Reference Intervals for Captive Saddleback Clownfish Amphiprion polymnus and Tomato Clownfish A. frenatus. Issue 1 (12th February 2021) - Wright, Sarah E.; Stacy, Nicole I.; Yanong, Roy P.; Juhl, Reilee N.; Lewbart, Gregory A.
Abstract: Reference intervals of blood analytes are important diagnostic tools that clinicians use as a basis for making clinical decisions and that have been documented for many fish species. Although the effects of dietary supplementation on hematology and blood biochemistry variables in clownfish have been shown, there are no published reference intervals to date for routine hematology and blood biochemistry panels for these popular cultured marine fish (including Amphiprion spp.). The objective of this study was to establish de novo reference intervals for selected hemogram data and, using whole‐blood analysis, commonly utilized chemistry analytes in two species of aquacultured clownfish: the Tomato Clownfish Amphiprion frenatus and Saddleback Clownfish A. polymnus . This study is based on blood samples from 25 clinically normal Tomato Clownfish and 38 clinically normal Saddleback Clownfish from two clownfish production facilities in Florida. Guidelines by the American Society for Veterinary Clinical Pathology were followed to generate robust reference intervals from the data collected. We report descriptive statistics and reference intervals for several hematology ( n = 12) and biochemistry ( n = 8) analytes using a small sample size and a small amount of blood per sample. The blood analyte data from this study are comparable with hematology and biochemistry data that have been reported in other teleost species. These results provide baseline health data for clownfish species that can be used in various clinical settings while also serving as a springboard for further research studies.